Manajemen Mutu Pendidikan dalam Meningkatkan Sumber Daya Manusia - Halimatus Sa’diyah (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2018)
School is a forum for improving the quality of human resources. Therefore, it is not surprising that education has been the problem that government has to find a common ground. School is an institution that is expected by the community, government and the state to create quality human resources. To create a quality school, it needs to be managed properly in accordance with the functions and goals of education itself. So that the output which is the focal point in education can play a role in accordance with the duties and functions according to the institution they do. Human resource management is equally important in the process of improving the quality of education in general. Therefore, the management of human resource also needs to be carried out optimally so that what is needed by individual, organizations or institutions can be achieved. In addition, good management of human resources in education will also answer challenges related to competitiveness, which is a problem in our country today.